Effects of low-level laser therapy on the orthodontic mini-implants stability: a systematic review and meta-analysis - Ana Carolina de Figueiredo Costa; Thays Allane Cordeiro Maia; Paulo Goberlânio de Barros Silva; Lucas Guimarães Abreu; Delane Viana Gondim; Pedro César Fernandes Santos (SpringerOpen, 2021)
Abstract Objectives The aim of this systematic review and meta-analysis was to assess the effects of low-level laser therapy (LLLT) on the orthodontic mini-implants (OMI) stability. Materials and methods An unrestricted electronic database search in PubMed, Science Direct, Embase, Scopus, Web of Science, Cochrane Library, LILACS, Google Scholar, and ClinicalTrials.gov and a hand search were performed up to December 2020. Randomized clinical trials (RCTs) or non-randomized clinical trials (Non-RCTs) that assessed the effects of LLLT on the OMI stability were included. Data regarding the general information, LLLT characteristics, and outcomes were extracted. The authors performed risk of bias assessment with Cochrane Collaboration's or ROBINS-I tool. Meta-analysis was also conducted. Results Five RCTs and one Non-RCT were included and 108 patients were evaluated. The LLLT characteristics presented different wavelength, power, energy density, irradiation time, and protocol duration. Five RCTs had a low risk of selection bias. Two RCTs had a low risk of performance and detection bias. All RCTs had a low risk of attrition bias, reporting bias and other bias. The Non-RCT presented a low risk of bias for all criteria, except for the bias in selection of participants. The meta-analysis revealed that LLLT significantly increased the OMI stability (p < 0.001, Cohen's d = 0.67) and the highest clinical benefit was showed after 1 (p < 0.001, Cohen's d = 0.75), 2 (p < 0.001, Cohen's d = 1.21), and 3 (p < 0.001, Cohen's d = 1.51) months of OMI placement. Conclusions LLLT shows positive effects on the OMI stability.